2020
DOI: 10.26866/jees.2020.20.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Design and Investigation of a Miniaturized Single-Layer ACS-Fed Dual Band Antenna for LTE and 5G Applications

Abstract: Presently, a single compact antenna is expected to operate in multiple frequency bands, so that it may be used for multiple applications. In this regard, a compact asymmetric coplanar strip (ACS) fed monopole antenna was designed to operate in LTE band-40 and 5G mid band frequencies. To achieve the desired dual band frequency, meander line radiating structure was used. The uniplanar design with the ACS feed considerably reduced the antenna size to 19.25 × 10.5 × 1.6 mm3. This miniaturized dual band antenna can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The resonance frequency was controlled by varying the electrical length of the slots. Some studies used asymmetric coplanar strip (ACS)-fed meander lines to ensure multiband operation, while avoiding the need for complex antenna geometries [8,9]. Defected ground structures (DGS) [10,11], stacked layers [12,13], parasitic elements [14,15], and metamaterials have also been employed to create multiband antennas [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The resonance frequency was controlled by varying the electrical length of the slots. Some studies used asymmetric coplanar strip (ACS)-fed meander lines to ensure multiband operation, while avoiding the need for complex antenna geometries [8,9]. Defected ground structures (DGS) [10,11], stacked layers [12,13], parasitic elements [14,15], and metamaterials have also been employed to create multiband antennas [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the proposed antennas are miniaturized enough to be mounted on a ground vehicle, they have narrow operating bandwidth characteristics because of the high Q value of the ESA [7]. Several methods have been studied to improve the operating bandwidth of the ESA [8][9][10][11][12][13][14][15]. In the studies [8][9][10][11][12][13], the antenna broadens the operating bandwidth by adding a multi-near-field resonant parasitic element.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been studied to improve the operating bandwidth of the ESA [8][9][10][11][12][13][14][15]. In the studies [8][9][10][11][12][13], the antenna broadens the operating bandwidth by adding a multi-near-field resonant parasitic element. However, in the studies [14,15], the active non-Foster circuit is used to widen the operating bandwidth of the antenna.…”
Section: Introductionmentioning
confidence: 99%
“…Various compact ACS‐fed antenna designs are discussed for multiband applications using different approaches such as adding radiating elements/branches 31–33 . Four E‐shaped meander line structures are added to the C‐shaped monopole antenna; it covers 4G LTE and 5G applications 34 . In Mansour et al, 35 a semi‐rectangular loop with a slot is proposed for dual‐band operation at 1.9 and 2.45 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…However, it does cover only single frequency band. From the above literature survey, it is observed that most of the existing antenna designs have the following issues: large size, narrow bandwidth, gain, ka, and less coverage of applications 22–42 . To address the above issues, a compact antenna design with a rectangular‐shaped split‐ring resonator (RSRR) structure is discussed.…”
Section: Introductionmentioning
confidence: 99%